Quantum Technologies: a Hermeneutic Technology Assessment Approach. - Possati, Luca M. (NanoEthics, 2024)
This paper develops a hermeneutic technology assessment of quantum technologies. It offers a “vision assessment” of quantum technologies that can eventually lead to socio-ethical analysis. Section 2 describes this methodological approach and in particular the concept of the hermeneutic circle applied to technology. Section 3 gives a generic overview of quantum technologies and their impacts. Sections 4 and 5 apply the hermeneutic technology assessment approach to the study of quantum technologies. Section 5 proposes distinguishing three levels in the analysis of the creation and communication of social meanings to quantum technologies: (a) fictions, (b) popularization, and (c) scientific journalism. Section 6 analyzes the results and defines some lines of action to increase social acceptance and trust in quantum technologies. The aim of this paper is to contribute to the debate on quantum technologies by enhancing the reflection on them and their potential, as well as illustrating the complexity of technological innovation and the need to shape it.